2010
DOI: 10.1016/j.addbeh.2009.12.006
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and validity of drug users' self reports of amphetamine use among primarily heroin and cocaine users

Abstract: Relatively few studies have addressed the psychometric properties of self-report measures of amphetamine use. This study examines the reliability and validity of the Risk Behavior Assessment's (RBA) lifetime and recent amphetamine-use questions. To evaluate validity, 4027 out-of-treatment primarily cocaine and heroin users provided urine samples that were compared to self-report data; to evaluate reliability, 218 completed the RBA at two time points, 48 hours apart. In the overall sample, self-reports demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(103 citation statements)
references
References 28 publications
(40 reference statements)
4
97
1
1
Order By: Relevance
“…Only one participant refused to do the urine analysis. Results were consistent with previous studies (e.g., Napper, Fisher, Johnson, & Wood, 2010;Project MATCH Research Group, 1997;Weiss et al, 1998), in that there were no discrepancies between urine analysis results and selfreported substance use.…”
Section: Methodssupporting
confidence: 91%
“…Only one participant refused to do the urine analysis. Results were consistent with previous studies (e.g., Napper, Fisher, Johnson, & Wood, 2010;Project MATCH Research Group, 1997;Weiss et al, 1998), in that there were no discrepancies between urine analysis results and selfreported substance use.…”
Section: Methodssupporting
confidence: 91%
“…By necessity, the study relied almost exclusively on measures of self-report. There is, however, an extensive international literature on self-reported drug use among heroin users, which has consistently demonstrated high reliability and validity in research settings (Jackson, Covell, Frisman, & Essock, 2005;Napper, Fisher, Johnson, & Wood, 2010). Whilst care should be taken in generalising the results to treatment systems outside Australia, the process of recruitment involved randomly selected treatment agencies stratified by modality and demographic characteristics and drug use histories were consistent with previous studies of heroin users in Australia and internationally (Darke, Topp, Kaye, & Hall, 2002;Gossop, Marsden, Stewart, & Rolfe, 2000;Hubbard, Craddock, Flynn, Anderson, & Etheridge, 1997).…”
Section: Discussionmentioning
confidence: 73%
“…To alleviate this potential problem, the adjusted analyses were performed after stratification by city and included city as an independent variable. (4) Self-reports of drug use could lead to an information bias, although studies have shown that self-reported drug use is both accurate and reliable [24,25]. (5) We assumed that the annual FOR was constant during the study period, which is supported by the lack of statistical differences in the NOR between participants at baseline and those with updated information during follow-up.…”
Section: Discussionmentioning
confidence: 99%